PROBLEM BASED LEARNING BERBANTUAN LEGO MENINGKATKAN PEMECAHAN MASALAH SISWA SEKOLAH DASAR - Zullya Ayu Malinda; Murtono Murtono; Eka Zuliana (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2017)
The purpose of classroom action research is to improve the students mathematic problem solving skills of grade IV SD 1 Kedungdowo through the problem based learning model assisted by lego. This research is a classroom action research with teacher research subject and 28 students. This study lasted for 2 cycles, each cycle consists of 4 stages of planning, action, observation and reflection. The independent variable in this research is lego assisted PBL. While the dependent variable in this research that is problem solving ability. Data collection techniques used is tests, observations, interviews and documentation. Data analysis used is quantitative and qualitative data analysis. The results showed that there was an increase of problem solving ability of mathematics in cycle I and Cycle II, that is from 70,92 (good) to 74,28 (good) with percentage of classical learning completeness equal to 64% to 86%. Supported by an increase in problem solving activity students score 2.51 (good) to 3.01 (good). In addition, teachers' skills in managing mathematics learning also increased by 74% (good) to 85% (very good).